On Doing an Analysis of Equity and Closing the Opportunity Gap - Verstegen, Deborah A. (Education Policy Analysis Archives, 2015)
Is public education equitable and does it provide an equal opportunity to all children and youths? Equity in public school funding is a critical issue facing all communities and has been addressed by the courts in all but five states. A key focus is on funding gaps between rich and poor school districts. Recently, attention has turned to the relationship between funding gaps and the opportunity gaps that have real and important impacts on student outcomes. This research provides a comprehensive analysis of equity in a western state of the U.S.A. Fifteen quantitative statistics, weighted for high-cost students, sparsity, district population, and the cost of education, are calculated and discussed. It was found that there are large opportunity gaps among school districts and they are linked to local wealth. This makes the quality of education a function of local wealth that abridges equal opportunities to learn and to be successful, for children and youth in schools and classrooms. Implications for closing the opportunity gap are discussed in the final section.